Katolikusok és protestánsok együttműködése a keresztény-nemzeti Magyarországért : az 1910-es és 1920-as évek fordulóján - Giczi, Zsolt (Közép-Európai Közlemények, 2013)
At the beginning of the 20th century the relationship between the Roman Catholic and Protestant Churches in Hungary had been characterised by tensions and debates, which flared up from time to time in the same way as all over the world. Nevertheless among the followers of both denominations there were people, who sought to reduce the denominational controversies and wanted to reach peaceful solutions. The bourgeois-democratic revolution of October, 1918 and the Hungarian Soviet Republik in 1919, created a fundamentally new social and political situation for all religious communities in Hungary. As a result, more and more people inside the Roman Catholic Church and the two most significant branches of the Hungarian Protestantism – the Reformed [Calvinistic] Church and the Evangelical-Lutheran Church – realised that the defence against those processes that threaten all of them couldn’t be successful without a denominational collaboration. For this reason happened from the end of 1918 numerous initiatives for the attainment of the common safeguarding of interests of the above mentioned three historical churches. After the collapse of the Bolshevik dictatorship the Churches became active supporters of the counter-revolutionary movement which came to power in the fall of 1919, because its leaders aimed at creating a Christian-Nationalist Hungary. At the beginning to the 1920’s Roman Catholics and Protestants collaborated successfully with each other in the fields of public and political life in order to organize the Christian-national system and to guarantee its existence. The Churches having great moral authority and social influence convinced millions of their followers of the legitimacy of the system and they mobilizied them to support it. Nevertheless the initially succesfull cooperation between the Roman Catholicism and Protestantism proved not to be stable. Although they succeeded in pushing the deep differences between them into the background for some time, but they had no success at all in solving them.